The Design of Student Service Information System to Print Grade Transcripts in the Industrial Engineering Study Program in Universitas Sebelas Maret Surakarta: Perancangan Sistem Informasi Pelayanan Mahasiswa Cetak Transkrip Nilai Di Program Studi Teknik Industri Universitas Sebelas Maret Surakarta - Hariyanto, Agus; Naury, Chairullah; Santosa, Eka Budhi (RADIANT: Journal of Applied, Social, and Education Studies, 2023)
The student service system at Universitas Sebelas Maret Surakarta (UNS), especially the print transcript of grades currently running, students can apply through three methods. The first method is done by filling out an application for a printed transcript. The second method is to use the Whatsapp application. The third method is done by using E-mail. Due to the large number of media used to apply for printed transcripts, the administrative unit of the study program cannot process all requests for print transcripts quickly. Sometimes there is a request to print a grade transcript that is not processed because the request data is overwritten with the new request data, so it is not readable by the study program administration unit. Based on the description of the background, it can be formulated that the problem to be solved in this research is "How to design a student service information system for printing transcripts in the Industrial Engineering study program of UNS". Limitations The problem that the author discusses in the study focuses more on the process of applying for transcripts of grades in the scope of the Industrial Engineering study program of UNS. The method used to design an information system for the print out of transcripts is using the System Development Life Cycle (SDLC) with the Waterfall model. The programming language used to design an information system for printing transcripts is PHP Native and MySQL database as data storage media. With the design of the information system for the application of printed transcripts, it is hoped that it can improve the quality of service to students, especially in the scope of the Industrial Engineering study program of UNS.